(untitled) (Agro Productividad, 2023)
The objective of the present study was to evaluate the effect of treatment, temperature and time using the minimum growth technique under in vitro conditions on stems with a length of 2 mm of Solanum quitoense. There were 8 treatments with different concentrations of mannitol, sucrose and Murashige and Skoog(1962) (0 ,5g L-1, 10 g L-1, 15 g L-1, 20 g L-1, 25 g L-1, 30 g L-1,30 g L-1), the experiments were placed in a room at 25 ºC and another at 21 ºC, the growth of the stem was recorded every fifteen days. The Generalized Linear Model showed that the treatments with the best results were those using 20 g L -1 and 30 g L-1 of mannitol in S. quitoense, which reduced in vitro growth in a remarkable way, preserving the characteristics of subsistence and vigor at a temperature of 21 ºC, while the applied concentrations of sucrose promoted rapid growth of the stem and shoots